4D Printed Auxetic Structures with Tunable Mechanical Properties - Yousuf, Mohammad Hani (2019)
A Master of Science thesis in Mechanical Engineering by Mohammad Hani Yousuf entitled, “4D Printed Auxetic Structures with Tunable Mechanical Properties”, submitted in June 2019. Thesis advisor is Dr. Wael Abuzaid. Soft and hard copy available.